BUSINESS PROCESS REENGINEERING SUPPLY CHAIN MANAGEMENT SYSTEM BASED BLOCKCHAIN USING BPR LC - Fikri Firdaus Tananto; Wellia Shinta Sari; Farrikh Alzami; Mira Nabila; Filmada Ocky Saputra; Chaerul Umam; Hasan Aminda Syafrudin; L.Budi Handoko (Jurnal Teknik Informatika (Jutif), 2023)
The agricultural sector in Indonesia is a superior sector compared to other sectors. The red onion commodity in Indonesia has the highest household consumption rate. Nowadays, technological developments are widely used to support existing agriculture to get maximum results. One of the technologies that can be used in agriculture is blockchain. The application of blockchain has gained importance in information systems and information technology research in the agricultural sector. However, in Indonesia, precisely in Central Java, there is no red onion supply chain management that uses blockchain technology for data storage, data security and data transparency. The author has a goal to re-engineer to overcome these problems by implementing blockchain technology using the Hyperledger Fabric and modeling business processes with Business Process Modeling Notation (BPMN). This research uses the Business Process Re-Engineering Life Cycle method in which this research produces red onion supply chain management with a new business process that is described by Business Process Modeling Notation (BPMN) and produces blockchain applications with various features and testing has been carried out using the Black box testing method with the result that existing features can run well without problems and the web application is running according to user needs to support supply chain management deficiencies so that they become more optimal and transparent in data storage.